Work Motivation, Organizational Support, and Employee Performance: The Mediating Role of Job Satisfaction - Aninda Nadya Bilqis; Khaeruman Khaeruman; Tata Rustandi (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to analyze the influence of work motivation and organizational support on employee performance through job satisfaction as a mediating variable at the Department of Agriculture and Food Security of Pandeglang Regency. Both factors are considered essential in improving job satisfaction and employee performance. This study employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires and analyzed using SmartPLS software. The research variables consisted of work motivation, organizational support, job satisfaction, and employee performance. The results indicate that work motivation has a positive and significant effect on employee performance (T-statistics = 4.406; P-values = 0.000) and job satisfaction (T-statistics = 7.485; P-values = 0.000). Organizational support also has a positive and significant effect on employee performance (T-statistics = 5.745; P-values = 0.000) and job satisfaction (T-statistics = 11.373; P-values = 0.000). Job satisfaction has a positive and significant effect on employee performance (T-statistics = 2.515; P-values = 0.012). Moreover, job satisfaction significantly mediates the effect of work motivation on employee performance (T-statistics = 2.356; P-values = 0.019) and the effect of organizational support on employee performance (T-statistics = 2.447; P-values = 0.015). All research hypotheses were supported. Organizational support emerged as the most dominant factor in enhancing job satisfaction, while employee performance was influenced both directly and indirectly through job satisfaction. These findings highlight the importance of strengthening work motivation and organizational support to optimize job satisfaction and employee performance